Market connections: Network support - Jagger, Sandeep; Barrett, Vernon (Technical Centre for Agricultural and Rural Cooperation, 2011)
CFCF uses GPS technology, smartphones, videos and the web to collect data on cocoa production. The organisation shares the information through a network of farmers, processing businesses and researchers to improve product quality and reach new markets